BUDAYA KERJA DI SEKOLAH TINGGI EKONOMI DAN BISNIS SYARIAH (STEBIS) INDO GLOBAL MANDIRI PALEMBANG - Nadia Okatari; Havis Aravik (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Types of jobs today vary widely in scope and size and may even have some practices that are unique to the job. Practices such as mentorship and internships also characterize most institutions in higher education. It is that the essence of working life is found in its culture. Work culture includes emotional and psychological climate or atmosphere. This may include employee morale, attitudes, and productivity levels. The work culture of each individual will determine the formation of the culture of the institution where he works. This article discusses the Work Culture at Syriah Indo Global Mandiri School of Economics and Business in Palembang. This article uses quantitative research, namely analyzing the theory of work culture at Syriah Indo Global Mandiri School of Economics and Business, Palembang. The results of this study are the importance of a productive work environment, open and honest communication, a fun atmosphere, as well as appreciation and motivation because with this a work culture can run well and the results carried out by employees are also better.